Development of Teaching Materials to Improve Student Learning Outcomes Using Learning Videos for Grade V Elementary School - Emi Liarni; Ramalis Hakim; Abna Hidayati; Zuwirna (Postgraduate, University of Mataram, 2026)
This research aims to develop video-based mathematics teaching materials for grade V elementary school students, as a solution to low learning outcomes and the use of conventional teaching materials that are less attractive. The development model used is ADDIE, which includes the analysis, design, development, implementation, and evaluation stages. The analysis was carried out by curriculum studies, observations, and interviews with teachers to find out the needs of students. The design stage involves planning materials, video structures, interactive quizzes, and contextual practice questions. Product development is validated by material, media, and language experts using Aiken's V analysis, which indicates all aspects are in the valid category. Implementation is carried out in learning to assess the effectiveness and practicality of teaching materials. The results of the study show that video teaching materials are effective in improving students' understanding of mathematics materials, and are considered practical and interesting by teachers and students. This product is able to present material visually, interactively, and relevant to daily life. Therefore, this video-based teaching material can be an alternative to improve the quality of mathematics learning in grade V of elementary school.